Settlement Dynamics and Factors Affecting Residence Selection in Population Density Settlements - M Fikri Amrullah; Endratno Budi Santosa; Muhammad Ansarullah S. Tabbu (Universitas Negeri Gorontalo, 2023)
Settlements are one of the fundamental necessities of life. The functions of settlements go far beyond just providing a place for rest and shelter. Settlements serve as spaces where social interactions occur, relationships between individuals and groups develop, and community identities are formed. Ngagelrejo is located in the densely populated Wonokromo district of Surabaya, and despite its high population density, it is an area that is in great demand for residential purposes. When considering land ownership status, the entire area consists of land without citizen ownership titles, commonly referred to as